2017
DOI: 10.1891/1541-6577.31.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Use of Family Planning Methods Among Heterosexual Mexican Couples

Abstract: The modified Spanish translation demonstrated usefulness for measuring barriers to family planning methods use in Mexico among heterosexual males and females of reproductive age. Barriers identified by Mexican women in this study may be addressed to reduce potential barriers to family planning among Mexican populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…A similar disparity in unmet need for family planning persists when comparing indigenous (21.5%) to non-indigenous (9%) women [13]. Other studies have found gender-specific differences in perceived barriers to care, with women more o en reporting medical concerns, stigma, and socioeconomic status as factors impeding utilization of contraception than men [14].…”
Section: Introductionmentioning
confidence: 90%
“…A similar disparity in unmet need for family planning persists when comparing indigenous (21.5%) to non-indigenous (9%) women [13]. Other studies have found gender-specific differences in perceived barriers to care, with women more o en reporting medical concerns, stigma, and socioeconomic status as factors impeding utilization of contraception than men [14].…”
Section: Introductionmentioning
confidence: 90%
“…Sebuah penelitian di Mexico menginformasikan temuan yang berbeda. Kemiskinan ditemukan sebagai barrieratau penghalang bagi pasangan usia subur untuk menggunakan alat kontrasepsi (Flores Arias et al, 2017). Hasil ini sejalan dengan penelitian di Ghana.…”
Section: Pembahasanunclassified